Phonetic Interference Changes of Arabic to Indonesian in Arabic Learning - Robiah, Siti; Mustofa, Tulus; Irhamuddin, Irhamuddin (STUDI ARAB, 2023)
The integration of Indonesian with other languages causes Indonesian to easily absorb various elements of foreign languages, Arabic has a strong influence and integration with Indonesian. This has caused a lot of Arabic to be absorbed in Indonesian, which is commonly found in some Indonesian vocabulary listed in KBBI, officially recorded to be used in full form by the people of Indonesia. The purpose of this study is to describe the form and see the phonetic changes that occur in the absorption elements of Arabic Indonesian vocabulary listed in the officially recorded KBBI. The method used in research is library research, using a qualitative approach, namely research that attaches importance to collecting qualitative data. The result of the study is that the acquisition of sounds in this language can be studied scientifically, so how to produce these sounds can be explained in more detail phonetically or phonetically. The absorption element of Arabic has a positive effect on Arabic language learning. This effect occurs when the vocabulary inherited from Arabic is not changed entirely, changing the sound and use of the language's words.